THE EFFECT OF TAX AVOIDANCE ON FIRM VALUE WITH CORPORATE RISK AS AN INTERVENING VARIABLE - Dewi Kusuma Wardani; Arisya Yaya Dwi Lestari (Universitas Tulungagung, 2026)
This study aims to analyze the effect of tax avoidance on firm value, with corporate risk as an intervening variable, among manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange during the 2015–2024 period. This study employs a quantitative approach using annual financial statements, yielding 171 observations through purposive sampling. Data analysis was conducted using the Partial Least Squares (PLS) method with the assistance of SmartPLS 3. The results indicate that tax avoidance has a positive effect on corporate risk and a negative effect on firm value. On the other hand, corporate risk does not affect firm value and fails to mediate the relationship between tax avoidance and firm value. These findings suggest that the effect of tax avoidance on firm value tends to occur directly, while investors appear to place greater emphasis on profit prospects than on the level of corporate risk when making investment decisions